COMPARATIVE ANALYSIS OF MORPHOLOGICAL AWARENESS BETWEEN EFL TEACHERS OF FORMAL AND NONFORMAL EDUCATION: A CASE STUDY - Lenni Novrianti Purba; Ratna Dewanti (Premise: Journal of English Education and Applied Linguistics, 2025)
The ability to dissect words into the smallest unit of language is not something many people can do. However, studies on linguistic awareness have shown that there is a correlation between morphological awareness (MA) and a language learner's level of language proficiency. This study aimed to investigate the morphological awareness of EFL teachers from formal and non-formal education; conventional school and English courses. The teachers-participants were selected from both institutions, tested with a morphological test, and interviewed to verify and confirm their MA test results. Descriptive statistic was used to analyze the results of tests and content analysis to analyze the interviews. Results of this study showed that the non-formal education EFL teachers demonstrated a better understanding of morphological knowledge than the formal education EFL teachers. Moreover, all teachers acknowledged the importance of morphological awareness in their language learning teaching. This study not only contributes to the growing area of morphology within the Indonesian context, but it also encourages teachers, particularly from formal education, to strengthen their understanding of morphological knowledge to design learning materials that fulfill students’ needs of morphological knowledge and awareness, and invites educators and policymakers to consider designing morphologically-focused content.